KONTRIBUSI USAHATANI PADI SAWAH TERHADAP PENDAPATAN KELUARGA PETANI DI DESA AMONGENA II KECAMATAN LANGOWAN TIMUR KABUPATEN MINAHASA (Contribution of Rice Farming to Farmer's Family Income in Amongena II Village, East Lan-gowan District, Minahasa Regency) - Sela Maluhima; Melsje Y. Memah; Martha M. Sendow (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
The purpose of this study was to analyze the income of farmers and the contribution ofÂ  rice farming to the income of farmer families in Amongena II Village, Langowan Timur District, Minahasa Regency. This research was conducted for 3 (three) months, starting from May to July 2019. The data used in this study were primary and secondary data. The results showed that the rice farming could provide a significant contribution to the family income in Amongena II Village with a percentage of 53% per planting season.Keywords: Income, Contributions, Rice Farming